2020
DOI: 10.1101/2020.05.15.098319
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stress induces divergent gene expression among lateral habenula efferent pathways

Abstract: The lateral habenula (LHb) integrates critical information regarding aversive stimuli that shapes decision making and behavioral responses. The three major LHb outputs innervate dorsal raphe nucleus (DRN), ventral tegmental area (VTA), and the rostromedial tegmental nucleus (RMTg). LHb neurons that project to these targets are segregated and nonoverlapping, and this led us to consider whether they have distinct molecular phenotypes and adaptations to stress exposure. In order to capture a time-locked profile o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…On the other hand, the loser-promoting dHbM projects to the ventral IPN, which then projects to the median raphe nucleus 27 . The mammalian LHb sends major afferent projections to the VTA and rostromedial tegmental area (RMTg) in addition to the DRN, and some studies have shown that LHb neurons respond to stress differently depending on its projection area 31,32 . Thus, it is likely that depending on the neural projection target, activation of LHb neurons can have different effects on aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the loser-promoting dHbM projects to the ventral IPN, which then projects to the median raphe nucleus 27 . The mammalian LHb sends major afferent projections to the VTA and rostromedial tegmental area (RMTg) in addition to the DRN, and some studies have shown that LHb neurons respond to stress differently depending on its projection area 31,32 . Thus, it is likely that depending on the neural projection target, activation of LHb neurons can have different effects on aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies need to be designed to record LHb firing rates prior to each 24-hr ethanol access period in the IAE paradigm to understand how LHb activity changes over time with chronic ethanol intake. It needs to be mentioned that our study was focused on individual differences in outbred rats with no other prior stress experience; and the next step would be to determine how baseline LHb neuronal activity and ethanol intake differs in rat with depression-like symptoms that have undergone stress [48][49][50] compared with normal rats.…”
Section: Discussionmentioning
confidence: 99%
“…RiboTag-associated RNA extraction as previously described. 30,46,47 The LHb was extracted using a midline 3 mm punch and homogenized After the final wash, HSB was removed and beads were re-suspended in 400 μL supplemented RLT buffer (10 μL β-mercaptoethanol/10 mL RLT Buffer) from the RNeasy Plus Micro Kit (Qiagen, Hilden, Germany) and vortexed vigorously. These samples were then placed back on the magnet and the RLT buffer was removed from the magnetic beads prior to RNA extraction.…”
Section: Ribotag Extractionmentioning
confidence: 99%
“…3,[25][26][27][28][29] Using intersectional expression of RiboTag to immunopurify ribosome-associated mRNAs selectively from each of these pathways in rats, we previously identified only small differences in gene expression between the neurons comprising these three pathways, suggesting that the regional target of LHb neurons is not defined by distinctions in neuronal phenotype. 30 LHb neurons are mostly glutamatergic, but numerous neuropeptides are also expressed in these neurons and these may be important in generating different patterns of output activity. 31 Recent gene array and single cell RNA sequencing studies in mice identified several clusters of similar neurons within LHb.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation